The virtuous reader : Old Testament narrative and interpretive virtue - Briggs, Richard, 1966- (Grand Rapids, Mich. : Baker Academic, 2010)
This volume offers a rich and thought-provoking portrait, or series of portraits, of the virtues required to read the Old Testament well. Biblical scholar Richard Briggs provides an exegetical exploration of "interpretive virtue" by carefully reading five Old Testament passages that reflect core virtues: humility, wisdom, trust, charity, and receptivity. The result is an example of theological interpretation that demonstrates the interplay between text and reader. Briggs approaches the biblical text with academic rigor and precision while maintaining an openness to the formative intentions of the biblical writers. - Publisher.
In pursuit of the virtues of the implied reader of the Old Testament -- Neither meek nor modest : the puzzling hermeneutics of humility -- Wisdom to discern the living interpretation from the dead -- Like a hermeneutic in a cage : the eclipse of biblical trust -- Love in the time of monotheism : the blessing of interpretive charity -- Summoned : the virtue of receptivity -- The virtuous reader of Old Testament narrative : from the implied reader to the real reader.
Includes bibliographical references (pages 213-254) and indexes.
Keywords: Bible -- Hermeneutics; Virtues; Bible; Hermeneutics; Virtues; Bible. -- 2; Vertu